Breaking Down Stress: Identifying Positive Aspects of Negative Situations - Schieber, Marquis Alexander (Wake Forest University, 2022)
The primary aim of the current study is to better understand people’s tendency to generate positive appraisals – subjective evaluations – of negative stressors. Specifically, whether the belief that positive and negative emotions can co-occur significantly predicts the number of positive aspects people can identify of a COVID related situation. In study 1, I tested the validity of the Dialectical Emotions Scale, which measures three separate beliefs: positive and negative emotions can co-occur (Pe+Ne), positive emotions can be found in negative/stressful situations (PeNS), and negative emotions can be found in positive situations (NePS). In study 2, I tested whether scores on each of these subscales in addition to general positivity, dispositional optimism, and extraversion, were significant predictors of the tendency to identify positive aspects of a COVID situation that participants were currently experiencing. Positivity and a low frequency of experiencing negative emotions were the strongest predictors of the tendency to identify positive aspects of negative stressors. Furthermore, the number of positive aspects people identified predicted how positive they felt after listing aspects of their situation controlling for how they felt at the start of the study and after describing their situation. The findings from this study present the possibility of an appraisal focused approach to dealing with stress.
Keywords: COVID-19; Positive appraisal; Positive Emotions; Stress